Axillary Nerve Block in Radial Open Reduction and Internal Fixation in Traumatic Brain Injury Patients: A Case Report - Nugroho, Wisnu Wahyu; Waloejo, Christrijogo Soemartono; Semedi, Bambang Pujo (Journal of Neonatal Surgery, 2025)
Patients with traumatic brain injury (TBI) and multi-trauma often require multiple surgical procedures, with prioritization based on urgency. Neurological impairment and hemodynamic instability pose significant challenges in delivering safe and optimal anesthetic management. A 23-year-old male presented with a basilar skull fracture, tension pneumocephalus, maxillofacial fractures, and a complete left forearm fracture. The patient underwent emergency craniotomy followed by elective internal fixation six days later using regional anesthesia with ultrasound-guided axillary peripheral nerve block (PNB). The block was performed using 0.5% ropivacaine and was confirmed successful by the absence of significant clinical or hemodynamic responses during surgery. This study shows that upper limb fracture fixation in patients with TBI can be safely performed using ultrasound-guided peripheral nerve block (PNB)-based regional anesthesia. The use of ropivacaine 0.5% provides optimal anesthetic effect with good hemodynamic stability and without significant complications. Postoperative monitoring revealed no local or systemic complications. Regional anesthesia with axillary PNB is a safe anesthetic modality for patients with upper extremity fractures and a history of TBI.